Proclamation by His Excellency, James Douglas, governor and commander-in-chief of Her Majesty's colony of Vancouver's Island and its dependencies [electronic resource]. - Vancouver Island (B.C.). Governor (1851-1863 : Douglas); Douglas, James, Sir, 1803-1877. ([S.l. : s.n., 1858)
With: Revocation of license of 30th May, 1838, to Hudson's Bay Company, for exclusive trading with the Indians, in so far as the same embraces the territories comprised in British Columbia. Dated: Given under my hand and seal at Victoria, Vancouver's Island, this third day of November, 1858 . Caption title. At head of title: British Columbia. Electronic reproduction. Mode of access: Internet. 44